Wednesday

October 1, 2014

October 1, 2014

Posted by **Lueshelle** on Wednesday, April 18, 2012 at 1:22pm.

- intermediate algebra -
**Henry**, Thursday, April 19, 2012 at 11:18pmUse the AC method.

A*C = 64(1) = (-8)(-8).

64a^2 + (-8ab-8ab) + b^3 =

Arrange the 4 terms to form 2 factorable pairs:

(64a^2-8ab)) + (-8ab+b^2) =

-8a(-8a+b) + b(-8a+b) =

(-8a+b)(-8a+b).

**Answer this Question**

**Related Questions**

intermediate algebra - Factor the expression 25x^2- 60xy+36y^2 into a product of...

algebra - factor the expression a^2-6ab+9b^2 into a product of binomials

algebra - Factor the expression 25x^2-60xy+36y^2 into a product of binomials.

algebra - Factor the expression 16x^2-72xy+81y^2 into a product of binomials.

algebra - factor the following expression into a product of two binomials. 64x^2...

math - Factor the expression 4x^2-20xy+25y^2 into a product of binomials

Alg I - Factoring ax^2 + bx + c Find two different values that complete each ...

math - Consider the following binomials. A=(x^2+5x) B=(6x+30) Part 1: Factor ...

math - Consider the following binomials. A=(x^2+5x) B=(6x+30) Part 1: Factor ...

math - Consider the following binomials. A=(x^2+5x) B=(6x+30) Part 1: Factor ...